Presence of p-synephrine in teas commercialized in Porto Alegre (RS/Brazil) - Marcelo Dutra Arbo; Paulini Braun; Mirna Bainy Leal; Elisa Raup Larentis; Ana Lucia Aboy; Rachel Picada Bulcão; Solange Cristina Garcia; Renata Pereira Limberger (Universidade de São Paulo, 2009)
Citrus aurantium (bitter orange) is characterized by the presence of p-synephrine, an amine structurally and pharmacologically related to ephedrine. Besides the same adverse effects as ephedrine, nowadays it is believed that altered levels of p-synephrine can be associated to the occurrence of migraine and cluster headaches. Leaves and fruits of this species are highly commercialized in form of teas and herbal preparations, but without taking into account the risks associated with its use. This work describes a survey of teas and herbal preparations containing C. aurantium, commercialized in Porto Alegre (RS/Brazil), in order to verify the presence of p-synephrine. Comparing with the mean amount available in the supermarkets, around 20% of the teas and 10% of the herbal preparations declared the presence of C. aurantium in their labels. In a sampling of 15 teas and 2 herbal preparations selected for the analysis, the presence of p-synephrine was characterized in all samples, with levels between 0.0040 to 0.2308%, leading to a caution that even being natural products, they are not free of adverse effects. Citrus aurantium (laranjeira-azeda) é caracterizada pela presença de p-sinefrina, amina estrutural e farmacologicamente similar à efedrina. Além de poder causar efeitos adversos similares aos da efedrina, atualmente acredita-se que níveis endógenos alterados de p-sinefrina possam estar associados à causa da enxaqueca. Folhas e frutos desta espécie são largamente comercializados na forma de chá e em preparados de erva-mate, sem que sejam considerados os riscos associados ao seu uso. Neste sentido, este trabalho descreve uma pesquisa em chás e preparados de erva-mate comercializados em Porto Alegre, para verificar a presença de C. aurantium e p-sinefrina. Comparando com a quantidade média disponível nas prateleiras dos supermercados, cerca de 20% dos chás e 10% dos preparados de erva-mate declaravam nos rótulos conter C. aurantium. De uma amostragem de 15 chás e 2 preparados de erva-mate selecionados para análise, em todos foi caracterizada a presença de p-sinefrina com níveis variando de 0,0040 a 0,2308%, levando ao alerta de que mesmo sendo naturais, estes produtos podem não ser destituídos de reações adversas.